Implementation of the Doelmatigheld Principle in Resolving Village Apparatus Selection Disputes in Klaten Regency - Kholik, Nur; Abadi, Muhammad Husnu; Subardjo, Subardjo; Muhammadi, Fauzan (Program Studi Hukum Keluarga Islam, 2024)
The screening selection mechanism for filling out village officials in Klaten District is regulated in Regent Regulation of Klaten District Number 30 of 2022 on Guidelines and Procedures for Appointing and Dismissing Village Apparatus. The said district regulation does not provide in detail the elucidation to be used as the solution. Seeing the various potential issues that may occur in the field, the legal basis for implementing the screening process in the form of Guidelines and Procedures for Appointment and Dismissal of Village Officials should regulate the methods and techniques for resolving disputes if they are to occur. This research aims to identify the implementation of the Doelmatigheld Principle in dispute resolution over examination results of village apparatus based on local wisdom in Klaten District. This is an empirical legal research with a normative juridical method. Additionally, the author also utilises a field study approach. The results of this research indicate that the principle of benefit is more relevant in decision making and local wisdom in Klaten District. This principle can also provide answers in dispute resolution over local wisdom-based village apparatus examination results in Klaten Regency that can be held accountable before the law.